2017
DOI: 10.1515/vzoo-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Bird Lice (Mallophaga, Philopteridae, Menoponidae) of Domestic Pigeons on Specialized Pigeon Breeding Farms in Poltava

Abstract: Bird Lice (Mallophaga, Philopteridae, Menoponidae) of Domestic Pigeons on Specialized Pigeon Breeding Farms in Poltava. Kolomak, I. O., Kruchynenko, O. V. -The species composition of pigeon lice parasitic on pigeons of ornamental breeds on the specialized closed-type farm (Poltava) was studied. Five species of these ectoparasites were registered: Columbicola columbae Linnaeus, 1758, Campanulotes compar Burmeister, 1838, (Philopteridae, Ischnocera), Bonomiella columbae Emerson, 1957, Hohorstiella lata Piaget, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a study researcher found two ecto-parasites on the pigeon both were lice species namely, Columbicola columbae and Chelopistes meleagridis, and occurred at the prevalence of 58% and 14%, respectively [4]. In another study identified four, five and seven species of ecto-parasites [5,6,7] but in present study found two species of ecto-parasites. The overall prevalence of gastrointestinal parasites in pigeon are founded that 43.34% in research area.…”
Section: Discussionmentioning
confidence: 55%
“…In a study researcher found two ecto-parasites on the pigeon both were lice species namely, Columbicola columbae and Chelopistes meleagridis, and occurred at the prevalence of 58% and 14%, respectively [4]. In another study identified four, five and seven species of ecto-parasites [5,6,7] but in present study found two species of ecto-parasites. The overall prevalence of gastrointestinal parasites in pigeon are founded that 43.34% in research area.…”
Section: Discussionmentioning
confidence: 55%
“…The rate of infestation with each species of lice recorded in the present study is higher than those recorded in Duhok which was 6% infestation with Columbicola columbae (17) and also in Bangladesh which was 21% (23). Studies performed in Spain (25), in Libya (24), in Iran (26,10), in Colombia (27), in Bangladesh (28) and in Ukraine (29) recorded rates of 100%, 82%, 79.41%, 78,40%, 64%, 50% and 100%, respectively. Also Ukraine (29) recorded higher infestation rate of Hohorstiella lata and Companulotes compar (72.7 and 41.8%, respectively) than the rates of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…C. turbinatum and C. columbae were reported from South-east region in Punjab, Pakistan (Ahmed et al, 2017). From neighboring and other countries, the prevalence of C. columbae in domestic pigeons in Tirunelveli district, India was 80.95% (Rani and Rajakumari, 2020) and the prevalence of B. columbae in domestic pigeons in Poltava region from Ukarine was 100% (Kolomak and Kruchynenko, 2017). In our study, 19.16% birds were infested with one spices of fly C. columbae and 45.83% of birds were infested with one species of fly P. canariensis.…”
Section: Discussionmentioning
confidence: 99%